DEHYDRATION BEHAVIORS OF INTERLAYER WATER IN SYNTHETIC BUSERITES - Choi H.S.; Kim S.J.; Kim J.J. (My University, 2004)
The structural changes of synthetic buserites (10Å phases), hydrous phyllomanganates, have been studied as a function of exchangeable interlayer cations and the relative humidity (RH) at which the sample is equilibrated. This study shows that the basal spacing of buserites and their-dehydration products vary depending on the nature of interlayer cations and water molecules. Na-buserite transforms directly to 7Å phase even in air dry. Cabuserite does not easily transform to 7Å phase even in a low RH. With increasing temperature, Mg-buserite transforms very slowly through progressive intermediate phases to 7Å phase at about 200°C, whereas Zn-buserite transforms directly to 7Å phase at about 60°C. Both Mg-and Zn-buserites do not dehydrate to 7Å phase even in a very low RH.